If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = x + -4 Reorder the terms: 4 + 3x = x + -4 Reorder the terms: 4 + 3x = -4 + x Solving 4 + 3x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + 3x + -1x = -4 + x + -1x Combine like terms: 3x + -1x = 2x 4 + 2x = -4 + x + -1x Combine like terms: x + -1x = 0 4 + 2x = -4 + 0 4 + 2x = -4 Add '-4' to each side of the equation. 4 + -4 + 2x = -4 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = -4 + -4 2x = -4 + -4 Combine like terms: -4 + -4 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 14-47=4(x-4)-5 | | 4x^2+5x+1=85 | | (x-18)/x=0.75 | | v+6=8/9 | | (18-x)/x=0.75 | | 5X+Y+Z=365 | | 5X+Y+Z=360 | | 3z-6=9z+18 | | -4v-12=8(v-9) | | 4a^9+4=0 | | (3y+2)(4y+1)=6y+5 | | 6x^2-30x+13=0 | | (2i+9j)+(7i-3j)= | | x^3-27/y^3=0 | | ln(x)=3/4 | | 4.8+x-5.9=3.6 | | 5(x+4)-4x=18-23 | | y=100-10(-63.24) | | 6+-6(3x+-1)=-42 | | 6+-6(3x+-1)=42 | | 3/5t+7=8 | | -7v-2=5v^2 | | -5.25r=332 | | 32-6x+7x=-15+28 | | 5(4z)-0.5z=234 | | 3/4x-6/7x=0 | | 53-5/8x=102 | | 16+x-11=18-5 | | 6y^3+3y^2-18y=0 | | 4ln(x)-3=0 | | 2x^2-19x-75=0 | | -x+1/2x=-1 |